Medium Optimization of the Production of Fructooligosaccharide by Aspergillus japonicus zz-1 Using Response Surface Methodology - Zhang, Yuan-Yuan; Nie, Shao-Ping; Wan, Cheng; Xie, Ming-Yong (Asian Journal of Chemistry, 2010)
This study leads to find the optimum compositions of medium for fructooligosaccharide production by Aspergillus japonicus zz-1 using the Plackett-Burman design and response surface methodology. The yield of fructooligosaccharide production determined by HPLC-ELSD was chosen as the response variable, while sucrose, yeast extract and NaNO3 were chosen as independent variables. The optimum medium condition was as follows: sucrose 140 g kg-1, yeast extract 50 g kg-1 and NaNO3 3 g kg-1. Under that condition, the yield of fructooligosaccharide reached 633 g kg-1. The Plackett-Burman design and response surface methodology were found to be useful and possessed advantage in optimizing the culture medium of fructooligosaccharide production comparing with traditional methods. The optimum medium condition was accurate and reliable.